MENGUATKAN KESADARAN MORAL SISWA SEKOLAH DASAR DENGAN INOVASI E-PEMBELAJARAN MELALUI WEBSITE INTERAKTIF MORALEDU - Setyo Wuri Kartika Nugraheni; Latifah Wulandari; Nur Kharisma Septiyan (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2025)
Education plays an important role in shaping individual character and morality, especially in today's digital era. With the increasing use of technology, the challenges of morality in the digital world are also increasingly complex, seen from phenomena such as cyberbullying and the spread of hoax information. This research develops MoralEdu, an interactive website designed to help elementary school students understand and internalize moral values. Through a qualitative approach and case study method, this research involved 24 students and the teacher of grade III of SDN Tambakbulusan. Data was collected through interviews and questionnaires, which showed that MoralEdu successfully improved students' understanding of moral values and changed their moral awareness. The questionnaire results showed a student satisfaction rate of 93.2%, indicating that the Platform is very useful in supporting moral learning. Despite challenges in access and training, MoralEdu has great potential to build moral awareness among the younger generation. Thus, the development and implementation of this Platform is expected to be a strategic step in creating a better learning environment and supporting positive character building among students.